Analisis Kesiapan Rumah Sakit Rafflesia Dalam Mengimplementasikan Electronic Medical Record (RME) Menggunakan Metode DOQ-IT - Syaputra, Reka Dwi; Agusianita , Agusianita (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda (JIPIKI), 2025)
It is important to evaluate readiness. Rafflesia hospital has implemented SIMRS, thus opening up opportunities for information system development through the implementation of RME. To achieve this, the readiness to use RME must be thoroughly evaluated. This research uses a descriptive approach. While the type of data obtained is primary data from medical and non-medical officers. HR readiness for RME implementation is 34, indicating that HR has not understood RME well, seeing that the benefits are lacking, especially in the IT field, and most officers do not know about RME. Organizational work culture is 31, indicating that there is an understanding that RME will change the work culture of the organization. When RME is used, there is a tendency to accept and support. In frequency 28, governance and leadership showed that there was an understanding of the value of electronic medical records in relation to IT management strategy and support and that decision makers were committed to implementing RME. In frequency 39, infrastructure indicates that information technology capacity is strong and the likelihood of successful RME adoption is high. In general, Rafflesia Hospital is well prepared to implement RME, as indicated by the RME Implementation Readiness Assessment Interpretation.